THE USE OF COOPERATIVE LEARNING MODEL FLIP CHART TYPE ON STUDENTS' COGNITIVE ABILITY IN HISTORY LEARNING CLASS XI SMA NEGERI 1 TAPUNG HULU: Penggunaan Model Pembelajaran Cooperative learning Tipe Flip Chart Terhadap Kemampuan Kognitif Siswa Pada Pembelajaran Sejarah Kelas XI SMA Negeri 1 Tapung Hulu - Adek Juni Rahayu; Bunari; Refli Surya Barkara (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to determine the effect of using the Cooperative Learning model with Flip Chart media on students' cognitive abilities in History learning for 11th-grade students at SMA Negeri 1 Tapung Hulu. The research employed a quantitative approach with a control group pretest-posttest experimental design. The population consisted of all 11th-grade students at SMA Negeri 1 Tapung Hulu, totaling 243 students from 8 classes. The sample comprised 30 students from class XI IPAS 3 as the experimental group and 30 students from class XI IPAS 5 as the control group. The research instrument was an objective test consisting of 50 questions, with 30 questions validated and demonstrating high reliability (0.706). Data analysis techniques included the Shapiro-Wilk normality test, homogeneity test, independent samples t-test, and N-Gain test to measure effectiveness. The results showed a significant improvement in the cognitive abilities of experimental class students, with mean scores increasing from 56.93 in the pretest to 82.03 in the posttest, while the control class increased from 51.9 to 67.53. The t-test results showed a significance value of 0.000 < 0.05, leading to the rejection of H₀ and acceptance of Hₐ, indicating a significant influence of the Cooperative Learning model with Flip Chart media on students' cognitive abilities. The N-Gain score of 0.5691 (57%) demonstrates that this learning model is moderately